Case report: Post-traumatic Tourette syndrome resolving with treatment of jugular venous narrowing; reconciling organic brain dysfunction following whiplash trauma with the absence of direct brain injury - Higgins, J. Nicholas P.; Kirker, Stephen (Frontiers in Neurology, 2023)
We describe a 33-year-old man who developed multiple symptoms, personality change and a severe tic disorder following a road traffic accident, which were undiminished for three years until jugular venous narrowing between the styloid process of the skull and the transverse process of the C1 vertebra was treated by surgical decompression. Immediately following surgery his abnormal movements almost completely resolved with no regression in five years of follow up. Vigorously debated at the time was whether or not his condition represented a functional disorder. Unrecognised throughout his illness, however, was a complaint of intermittent, profuse discharge of clear fluid from his nose, beginning on the day of the accident, continuing up to the time of surgery, after which it was very substantially reduced. This outcome reinforces the idea that jugular venous narrowing can cause or perpetuate a cerebrospinal fluid leak. It suggests that the interaction between these two pathological defects may have a profound effect on brain function in the absence of any demonstrable brain lesion. It invites a re-evaluation of normal head and neck venous anatomy. It should strike a cautionary note in the diagnosis of functional illness. It invites exploration of a remediable structural cause for Tourette syndrome.